2024
DOI: 10.1021/acs.iecr.3c03708
|View full text |Cite
|
Sign up to set email alerts
|

SO2 Capture and Detection by SBA-15 and Amine-Functionalized SBA-15

Juan L. Obeso,
Valeria B. López-Cervantes,
Reyna Ojeda-López
et al.

Abstract: An exploration of the SO 2 adsorption properties, of two distinct mesoporous materials, classic hydroxy-functionalized SBA-15 and amino-functionalized SBA-15, shows remarkable SO 2 adsorption properties, with total uptakes of 4.43 and 4.19 mmol g −1 at 298 K and 1 bar, respectively. Furthermore, the amino-functionalization increases the SO 2 adsorption at low pressure. Relatively weak SO 2 interactions via physisorption processes in both materials were corroborated by calculating the heat of adsorption for SO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…10 In fact, the effect of silicate modification on SO 2 adsorption has been studied, showing that the capture performance of amine-modified silicates is significantly higher than that of silicates modified with metals. 11 It may be related to the basic character of the amine. It has even been reported that optimally increasing the amount of amine positively affects the adsorbent performance.…”
Section: Introductionmentioning
confidence: 99%
“…10 In fact, the effect of silicate modification on SO 2 adsorption has been studied, showing that the capture performance of amine-modified silicates is significantly higher than that of silicates modified with metals. 11 It may be related to the basic character of the amine. It has even been reported that optimally increasing the amount of amine positively affects the adsorbent performance.…”
Section: Introductionmentioning
confidence: 99%